EFFECT OF KECOMBRANG ETHANOL EXTRACT (ETLINGERA ELATIOR) ON FUSOBACTERIUM NUCLEATUM BIOFILM DEGRAGATION - Fanni Kusuma Djati; Meylida Ichsyani; A. Haris Budi Widodo; Aisha Tiara Dewi (Universitas Muhammadiyah Surakarta, 2025)
Fusobacterium nucleatum is a Gram-negative anaerobic bacterium that plays a crucial role in periodontal disease progression through biofilm formation. Kecombrang (Etlingera elatior) is a traditional medicinal plant containing bioactive compounds with antimicrobial properties. This study aimed to evaluate the effect of kecombrang extract on F. nucleatum biofilm degradation. This experimental study used ethanolic extracts from three parts of kecombrang (leaves, stems, and flowers) at concentrations of 1.56, 3.12, 6.25, 12.50, 25, and 50 mg/mL. F. nucleatum biofilm was formed and treated with various extract concentrations. Chlorhexidine 0.2% was used as positive control and DMSO 1% as negative control. Biofilm degradation percentage was measured using crystal violet assay at 490 nm wavelength. Data were analyzed using Two-Way ANOVA to evaluate the main effects of plant parts and extract concentrations, followed by Tukey’s HSD post-hoc test. All kecombrang extracts showed dose-dependent biofilm degradation activity. Flower extract demonstrated the highest efficacy with degradation percentages ranging from 36.37% to 86.22% at concentrations 1.56-25 mg/mL. Leaf extract showed degradation of 38.2—82.08%, while the stem extract achieved 34.00-80.22% degradation at the same concentration range. The MBEC50 values were 2.62 mg/mL for flower extract, 3.68 mg/mL for leaf extract, and 4.99 mg/mL for stem extract. Kecombrang extracts possess significant biofilm degradation activity against F. nucleatum, with flower extract showing the most promising results comparable to chlorhexidine positive control